The Use of Literature Circle Technique in Teachers’ Professional Development - Avci, Süleyman; Özgenel, Mustafa (Asian Journal of Education and Training, 2019)
Supporting teachers for their professional development is important. Literature circle technique has a potential to create and support professional learning communities. The purpose of this research was to examine how the literature circle can be used between teachers in order to enhance their professional development. In this qualitative study the action research approach was employed. The participants of the study were seven teachers working in a vocational high school in İstanbul. The duration of the study was one year. The teachers of different subject areas read nine books using the literature circle technique. They decided which books they were going to read together, read the same book and parts, organized 2-hour discussions weekly and attended the discussions after they had delivered the technical tasks. The research data was collected with focus group interviews, questionnaire form and field notes. The research findings showed that literature circle is suitable for teachers and can be used in professional learning communities. The teachers liked it very much as it provided retentive learning, allowed for learning from each other and made literature more effective. The teachers emphasized that they noticed the individual differences among the students and started to use suitable methods thanks to the technique. The literature circle technique provided teachers with an opportunity to better know each other, share experiences and opinions about day to day teaching practices.